2022
DOI: 10.3390/coatings12121862
|View full text |Cite
|
Sign up to set email alerts
|

Element Differential Method for Non-Fourier Heat Conduction in the Convective-Radiative Fin with Mixed Boundary Conditions

Abstract: Fin is an efficient and straightforward way to enhance heat transfer rate. When the heat source varies dramatically in a very short time, non-Fourier heat conduction should be considered. In the paper, taking advantage of numerical stability and no integral and easy-to-implement features of an element differential method, a numerical model is developed to evaluate the fin efficiency of the convective-radiative fin within non-Fourier heat conduction. In this fin, heat is generated by an internal heat source and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Ma et al. [37] probed the efficiency of convective‐radiative extended surface in the presence of periodic boundary conditions. Machine learning (ML), a branch of artificial intelligence, has advanced rapidly nowadays.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ma et al. [37] probed the efficiency of convective‐radiative extended surface in the presence of periodic boundary conditions. Machine learning (ML), a branch of artificial intelligence, has advanced rapidly nowadays.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal attributes of an extended surface with periodic heat transfer were analyzed by Souayeh and Abro [36]. Ma et al [37] probed the efficiency of convective-radiative extended surface in the presence of periodic boundary conditions. Machine learning (ML), a branch of artificial intelli-gence, has advanced rapidly nowadays.…”
mentioning
confidence: 99%
“…The structure of a heat exchanger affects its heat transfer performance. Studies have shown that heat exchanger optimization can be achieved by optimizing and improving the heat exchanger structure [6,7]. Mario et al [8] obtained locally optimized fin patterns by considering the topology optimization of plate-fin heat exchangers.…”
Section: Introductionmentioning
confidence: 99%